Pengaruh Struktur Modal dan Likuiditas terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019–2023 - Sofia Ranti Rahmah Riska Hidayat; Deasy Tantriana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This study aims to examine the influence of capital structure and liquidity on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Capital structure is represented by the Debt to Equity Ratio (DER), while liquidity is measured using the Current Ratio (CR). Profitability is assessed through Return on Assets (ROA) and Return on Equity (ROE). This research employs a quantitative approach with a causality design and uses multiple linear regression as the analytical method. The sample consists of three manufacturing companies—PT Chandra Asri Pacific Tbk (TPIA), PT Aneka Tambang Tbk (ANTM), and PT Gudang Garam Tbk (GGRM)—selected through purposive sampling based on predetermined criteria. Prior to hypothesis testing, classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation were conducted, and all variables met the requirements for regression analysis. The findings reveal that DER has a negative and significant effect on both ROA and ROE, indicating that higher leverage reduces the company’s ability to generate profits. Conversely, CR has a positive and significant effect on profitability, suggesting that companies with stronger liquidity positions are more capable of sustaining operational activities and improving financial performance. The F-test results show that DER and CR simultaneously have a significant influence on profitability. Furthermore, the coefficient of determination demonstrates that more than half of the variation in profitability can be explained by the two independent variables. Overall, the study emphasizes the importance of maintaining an optimal balance between debt utilization and liquidity management. Effective capital structure policies and sufficient liquidity levels are essential for enhancing profitability and ensuring financial stability within the manufacturing industry. These findings provide valuable implications for corporate decision-makers, investors, and stakeholders in formulating financial strategies that support long-term performan.